In vitro susceptibility of Staphylococcus aureus to porphyrin-silver mediated photodynamic antimicrobial chemotherapy - Shabangu, Samuel Malewa (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
This work reports on the syntheses and characterization of symmetrical and unsymmetrical porphyrin complexes namely, 5,10,15,20-tetra(4-pyridyl)-porphyrinato zinc(II) (1), 5,10,15,20-tetrathienyl porphyrinato zinc(II) (2), 5-(4-hydroxyphenyl)-10, 15, 20-tris(2-thienyl) porphyrinato zinc(II) (3), 5-(4-carboxyphenyl)-10,15,20-tris(pentafluorophenyl)- porphyrinato zinc(II) (4), 5-(4-carboxyphenyl)-10,15,20-triphenyl-porphyrinato zinc(II) (5) and 5-(4-carboxyphenyl)-10, 15, 20-tris(2-thienyl)-porphyrinato zinc(II) (6). The synthesis of silver nanoparticles (AgNPs) was also undertaken in this research work. Complexes 1, 2, 3 and 6 were linked to oleic acid/oleylamine functionalized nanoparticles via self-assembly and 4-6 were linked via covalent interaction through an amide bond to glutathione capped AgNPs. The effect of nature of bond along with symmetry were investigated, of interest were the five membered thienyl substituents. The photophysical and photochemical behaviour of the complexes and their conjugates with AgNPs were investigated in dimethylformamide. The porphyrin and AgNPs conjugates afforded an increase in singlet oxygen quantum yield. Complexes 1-6 and their conjugates were used for photodynamic antimicrobial chemotherapy of Staphylococcus aureus. The antimicrobial studies were done in two different concentrations of 0.36 and 2.0 Î¼g/mL. The thienyl substituted porphyrin complexes and their conjugates gave better photodynamic activity as compared to phenyl analogues
Keywords: Porphyrins; Nanoparticles; Photochemotherapy; Drug resistance in microorganisms; Staphylococcus aureus